Estimation of YKL-40 acute-phase protein in serum of patients with periodontal disease and healthy individuals: A clinical-biochemical study - Vinay Chavan; Srinu Sabavath; C Hemachandra Babu; Laxman Boyapati (Wolters Kluwer Medknow Publications, 2019)
Objective: YKL-40, an acute-phase protein, is a novel potential inflammatory marker. It is a member of "mammalian chitinase-like proteins." YKL-40 is secreted by activated neutrophils and macrophages in both acute and chronic inflammation. It is also shown to be produced by vascular smooth muscle and endothelial cells, arthritic chondrocytes, cancer cells, and embryonic and fetal cells. It might play an important role in the initiation or maintenance of pro-inflammatory response. The purpose of the present study was to estimate the concentrations of YKL-40 in the serum of healthy and periodontally affected individuals. Materials and Methods: Serum samples were collected from forty patients of periodontally (Group C) affected sites (probing depth [PD] >5 mm) and gingivitis patients (Group B) affected sites (PD ≤ 3 mm) with bleeding on probing. Comparison with healthy controls was carried out by collecting serum samples from ten healthy volunteers (Group A). 5 ml of blood was collected from the antecubital fossa by venipuncture using a 20G needle with 5 ml syringe and immediately transferred to the laboratory. Serum was extracted from blood and stored at −70°C till the assay procedure, and enzyme-linked immunosorbent assay was performed to determine the concentrations of YKL-40. Results: The mean YKL-40 concentration scores were significantly higher in Group C, i.e. 62.49 ± 8.33 when compared to Group B, i.e. 51.96 ± 4.30 and Group I, i.e. 44.23 ± 4.34, which was statistically significant (P ≤ 0.001). In the present study, mean probing pocket depth was higher in Group C than Group A (P ≤ 0.001). A positive correlation was found between probing pocket depth and concentrations of YKL-40 in serum (r = 0.815), P < 0.001, i.e. when the pocket depth increases, concentration of YKL-40 also increases. Conclusion: In this study the presence of YKL-40 in serum samples was observed both in healthy and chronic periodontitis. In this study, the concentration of YKL-40 was elevated in chronic periodontitis group when compared to healthy group. With increases in the amount of destruction, there is substantial increase in clinical parameter and YKL-40 concentration in serum, which is directly related to pocket depth. This study shows that YKL-40 is a novel biomarker for periodontal disease progression.